Technology, Governance, and a Sustainability Model for Small and Medium-Sized Towns in Europe - Sousa, María José; Mercade-Mele, Pere; Molina-Gómez, Jesús (MDPI, 2020)
New and cutting-edge technologies causing deep changes in societies, playing the role of game modifiers, and having a significant impact on global markets in small and medium-sized towns in Europe (SMSTEs) are the focus of this research. In this context, an analysis was carried out to identify the main dimensions of a model for promoting innovation in SMSTEs. The literature review on the main dimensions boosting the innovation in SMSTEs and the methodological approach was the application of a survey directed to experts on this issue. The findings from the literature review reflect that technologies, governance, and sustainability dimensions are enablers of SMSTEs’ innovation, and based on the results of the survey, a model was implemented to boost innovation, being this the major add-on of this research.
Keywords: Innovaciones tecnológicas; SMSTEs; Innovation; Digital; Governance; sustainability